La riforma universitaria nel quadro dei sistemi di governance europei - Regini, Marino (Lectio Magistralis, 2014)
Over the past 30 years, all European countries have been affected by reorganization processes concerning their higher education systems. In this volume, two aspects of this type of reorganization are discussed: changes in governance models and differentiation processes within the various higher education systems. The new governance models of higher education systems are based on three pillars: autonomy, evaluation and competition. Everywhere, universities were managed in a more business-like fashion, strengthening the central leadership and reducing the power of the collective bodies. In Italy, autonomy has developed in a distorted way, and for a long time has not been accompanied by evaluation and competition. In addition to reforming governance, European governments have responded to the students' mass demand for university access with different backgrounds and ambitions, differentiating the higher education systems in the concerned countries. There was a first surge of differentiation in the 1960s and 1970s, and a second one took place in the late 1990s. Italy was an exception, and in this lies the origin of most of the problems of Italian universities, which the volume discusses while also offering possible solutions.